2021
DOI: 10.1177/10778012211054866
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Focused Coping Strategies Used by Victims of Gender Violence Across the Stages of Change

Abstract: This study compares the problem-focused emotion regulation strategies used by 200 female survivors of intimate partner violence (age: M = 40.16, SD  =  11.27, 18 – 66 years) to cope with violence throughout various stages of change (SOC). It examines the relationship between problem-focused coping strategies and positive and negative affect, and the impact of these variables on the different SOC. Results suggest that victims differ and are flexible in the use of strategies throughout the various SOC. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
1
6
0
2
Order By: Relevance
“…In any case, these results support the utility of using an intra-individual approach in the study of coping strategies as opposed to trans-transituational models that assume the functionality or dysfunctionality of the strategies without taking into account the context in which they are used ( Waldrop and Resick, 2004 ; Puente-Martinez et al, 2021 ). In this study, it has been found that under circumstances of violence maintained over time in different relationships, in women with low social support and younger age, the victims are more likely to use strategies of reevaluation of the situation to adapt to it in the short term, although this could mean maintaining the situation of violence.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…In any case, these results support the utility of using an intra-individual approach in the study of coping strategies as opposed to trans-transituational models that assume the functionality or dysfunctionality of the strategies without taking into account the context in which they are used ( Waldrop and Resick, 2004 ; Puente-Martinez et al, 2021 ). In this study, it has been found that under circumstances of violence maintained over time in different relationships, in women with low social support and younger age, the victims are more likely to use strategies of reevaluation of the situation to adapt to it in the short term, although this could mean maintaining the situation of violence.…”
Section: Discussionsupporting
confidence: 57%
“…Social or interpersonal resources, mainly assessed through the perceived social support of IPV victims, have also frequently been included among the predictors associated with revictimization in gender-based violence and in most studies they are given a mainly protective role ( Goodman et al, 2005 ; Valentine et al, 2016 ; Ogbe et al, 2020 ; Ørke et al, 2020 ). Finally, with respect to emotional resources, there is a line of research which has focused on exploring the victims’ use of both emotional regulation and coping strategies in the face of stress to mitigate the consequences of IPV ( Crowe and Murray, 2015 ; Puente-Martinez et al, 2021 ). Even so, the evidence that has analyzed emotional regulation and coping processes in the population of IPV victims is scarce and heterogeneous when compared with the high number of studies conducted to examine the role of material and interpersonal resources ( Keeling et al, 2016 ; Orke et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations